Can Degrowth Overcome the Leakage Problem of Unilateral Climate Policy? - Mario Larch; Markus Löning; Joschka Wanner (Center for Economic Studies and ifo Institute (CESifo), 2017)
Unilateral climate policy suffers from carbon leakage, i.e. the (partial) offset of the initial emission reduction by increases in other countries. Different than most typically discussed climate policies, degrowth not only aims at reducing the fossil fuel use in an economy, but rather at a reduction of all factor inputs, which may lead to different leakage implications. We conduct the first investigation of degrowth in a multi-country setting in order to (i) compare the leakage effects of national pure emission reduction policies to degrowth scenarios, (ii) identify underlying channels by decomposing the implied emission changes into scale, composition, and technique effects, and (iii) investigate which country characteristics determine degrowth's relative effectiveness to overcome the leakage problem. Using a structural gravity model, we find that degrowth indeed significantly reduces leakage by keeping the sectoral composition of the country more stable and reducing uncommitted countries' incentives to shift towards more energy-intensive production techniques. The higher effectiveness of degrowth in reducing carbon emissions is most pronounced for small and trade-open economies with comparatively clean production technologies.
Keywords: F18; Q54; Q57; 330; degrowth; climate policy; gravity model; carbon leakage